La Cartografia ISTAT come supporto per le emergenze territoriali - Mugnoli, Stefano; Abbatini, Damiano; Chiocchini, Raffaella; Lipizzi, Fabio (GEOmedia, 2016)
Official ISTAT Cartography and its related data, updated in advance of each census survey, not only represent the base for statistical description of the entire Italian territory but can be used as an useful help in emergency situation too. Their partition into residential and production areas and enumeration areas, in fact, allows to realize thematic maps, through very simple GIS algorithm, very useful overall during the early stages of the emergency. Buildings and houses ISTAT database can further provide some specific information about buildings and houses state (Census 2011 data).